2012
DOI: 10.1007/s10144-012-0332-7
|View full text |Cite
|
Sign up to set email alerts
|

Leading‐edge populations do not show low genetic diversity or high differentiation in a wind‐pollinated tree

Abstract: Climate changes can shift species' ranges. Knowledge on genetic variation of the leading-edge populations provides critical information to understand responses and adaptation of plants to projected climate warming. To date, the research into genetic variation of leading-edge populations has been limited, particularly in the role of wind-mediated pollen flow in maintaining high genetic variation. Castanopsis sclerophylla (Fagaceae) is a wind-pollinated and gravity-dispersed tree. In the present study, we used s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…). Similar patterns consistent with the C‐M hypothesis have been reported elsewhere, for example, in Ulmus laevis (Finland and Estonia), Leavenworthia stylosa (USA) and Arenaria provincialis (France) (Vakkari et al ., ; Dixon et al ., ; Pouget et al ., ), but studies in south and east China have not found such evidence (Ge et al ., ; Shi & Chen, ; Shi et al ., ). Then again, different plant species within a given region do not always show genetic patterns consistent with the C‐M hypothesis (Jump et al ., ; Diniz‐Filho et al ., ; Soares et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). Similar patterns consistent with the C‐M hypothesis have been reported elsewhere, for example, in Ulmus laevis (Finland and Estonia), Leavenworthia stylosa (USA) and Arenaria provincialis (France) (Vakkari et al ., ; Dixon et al ., ; Pouget et al ., ), but studies in south and east China have not found such evidence (Ge et al ., ; Shi & Chen, ; Shi et al ., ). Then again, different plant species within a given region do not always show genetic patterns consistent with the C‐M hypothesis (Jump et al ., ; Diniz‐Filho et al ., ; Soares et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…topography). Shi & Chen () found evidence for post‐glacial expansion to north, but they demonstrated an increasing trend of genetic diversity towards leading‐edge populations of Castanopsis sclerophylla . Second, the high‐latitude‐skewed C‐M pattern may have been shaped by the complex topography in the species' distribution range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, such high and uniform levels of genetic diversity across a species' entire range have already been observed for many temperate trees (for a review see Jaramillo-Correa et al, 2009). In wind-pollinated trees, even higher levels of diversity can be reached when pollen-mediated gene flow constantly brings alleles from source populations to the colonization front (Shi and Chen, 2012). Moreover, in the case of a gradual expansion of a migrating front, neither a population bottleneck nor spatial genetic structure caused by isolation by distance (IBD) would be expected to occur because of the substantial gene flow that would effectively homogenize the newly established populations.…”
Section: Introductionmentioning
confidence: 91%
“…This heterogeneity is represented across studies of tree species. Empirical studies have found both lower genetic diversity (Mimura & Aitken, 2007;Marsico et al, 2009;Kitamura et al, 2015;Johnson et al, 2017) and similar or higher genetic diversity (Born et al, 2008;Pluess, 2011;Shi & Chen, 2012) in leading edge populations of tree species after range expansion. Temperate forest tree species are generally associated with high gene flow via wind-borne pollen across large geographic distances (Kremer et al, 2012), as well as a long life span and juvenile phase.…”
Section: Introductionmentioning
confidence: 99%